Evaluating the effectiveness of land use management as a natural flood management intervention in reducing the impact of flooding for an upland catchment. Issue 4 (23rd April 2023) - Kingsbury‐Smith, Lorna; Willis, Thomas; Smith, Mark; Boisgontier, Hélène; Turner, Daniel; Hirst, Jack; Kirkby, Michael; Klaar, Megan
Abstract: Natural flood management (NFM) is a method for reducing flooding by using a catchment‐based approach to managing flood risk. Understanding and quantifying the impact of implementing NFM at the catchment scale remains ambiguous with a clear need for robust empirical evidence. A combination of fieldwork, laboratory analysis and modelling was applied to quantify the impacts of land use management changes on catchment flood hazard. Soil hydraulic conductivity was measured under varying land management regimes and used to parameterize a physically based spatially distributed hydrological model (SD‐TOPMODEL). A suite of stakeholder informed land management scenarios was modelled, permitting the quantification of the impact of NFM interventions on the timing and the intensity of the peak discharge at the catchment outlet. The findings support the implementation of NFM interventions as a means of reducing flood hazard within a rural upland catchment. Improved soil infiltration provided the greatest reduction in the intensity and delayed timing of the flood peak for a 10‐year occurrence storm event (7% reduction in peak runoff and 8% increase in lag time) with similar reductions observed for a 100‐year storm event. Catchment wide woodland planting reduced peak flow by 11% during the 100‐year event but was not effective during the 10‐year event. Riparian buffer strips provided consistent reductions in peak flow and in the timing of the peak across both storm events with no significant differences relating to vegetation age. Critically, we observed that the effect of implementing multiple NFM interventions was not additive and that efficiencies can be made in using this modelling approach to prioritize the most effective outcomes. Abstract : A combination of fieldwork, laboratory analysis and modelling was applied to quantify the impacts of land use management changes on catchment flood hazard, using a spatial distributed version of the hydrological model, TOPMODEL. The findings support the implementation of natural flood management interventions as a means of reducing flood hazard within a rural upland catchment, with reductions of 11% peak flows for a 1 in 100‐year event.